INTERVENTIONS IN THE MANAGEMENT OF FATIGUE AND QUALITY OF LIFE IN PATIENTS UNDERGOING CHEMOTHERAPY: REVIEW STUDY - Lorena Campos Mendes; Elizabeth Barichello (Universidade Federal do Paraná, 2019)
Objective: to identify in the literature the non-pharmacological interventions used in the management of oncological fatigue and Quality of Life of patients with digestive neoplasia undergoing chemotherapy.Method: this was an integrative review. The MEDLINE, PubMed, Scopus, CINAHL and Web of Science databases were used. Articles in Portuguese, English or Spanish, published between 2013-2018, which described the use of non-pharmacological interventions for oncological fatigue and/or Quality of Life of patients with digestive system neoplasms undergoing chemotherapy were selected.Results: Of the total of 278 articles retrieved, six were selected. Regarding the language, all were in English. Among the clinical trials, only one scored 5 on the Jadad Quality Scale. The studies indicated the use of physical activity programs as being effective.Conclusion: the practice of physical activity was considered an effective intervention, while acupuncture did not present a viable clinical response in the management of oncological fatigue and Quality of Life.